2016
DOI: 10.1016/j.jpeds.2016.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Histamine-2 Receptor Antagonist and Proton Pump Inhibitor Treatment at United States Children's Hospitals

Abstract: Objective To determine treatment frequency and duration of H2RA/PPI use among infants hospitalized within US children’s hospital NICUs and evaluate diagnoses/demographic factors associated with use. Study design We retrospectively analyzed a cohort of NICU infants admitted to 43 US children’s hospitals within the Pediatric Health Information System (PHIS) database between January 2006-March 2013 to determine H2RA/PPI treatment frequency, timing/duration of treatment, factors associated with use, percent of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 55 publications
0
47
0
Order By: Relevance
“…A recent study examining 43 NICUs in the United States found that 24% of admitted infants received an acid suppression medication during the hospitalization. 2 Extremely premature infants and those with a congenital abnormality were most likely to be prescribed acid suppression therapy. 2 The high treatment rates in these populations may be due to greater concern for GER-induced aerodigestive disease or acid-mediated stress ulceration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study examining 43 NICUs in the United States found that 24% of admitted infants received an acid suppression medication during the hospitalization. 2 Extremely premature infants and those with a congenital abnormality were most likely to be prescribed acid suppression therapy. 2 The high treatment rates in these populations may be due to greater concern for GER-induced aerodigestive disease or acid-mediated stress ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…1 A recent report estimates that 25% of preterm infants receive either omeprazole or ranitidine during their NICU hospitalization. 2 However, current evidence-based guidelines recommend that these medications be used "sparingly if at all" in preterm infants. 1 The available data indicate that acid suppression medications are ineffective at controlling clinically perceived signs of GER in infants 3 and that their use may result in serious adverse effects.…”
mentioning
confidence: 99%
“…This intervention may not be generalizable to NICUs that care for a different patient mix (for example, nonsurgical cases or primarily inborn infants) or in which rates of PPI/H2RA use are already low; although, the baseline rate of acid-suppressing medication use and indications for prescription in our unit were remarkably similar to other published series including units with widely varying patient populations. 1,2 Development of any guideline for acid-suppressing medications in neonates is limited by the poor quality of available efficacy data, and it could be argued that there are no indications for PPI/H2RA use in the NICU that are supported by high-quality evidence. Nevertheless, even with the inclusion of some controversial indications in our guideline, we were able to significantly impact prescription rates.…”
Section: Discussionmentioning
confidence: 99%
“…8 Acid-suppressing medications are most commonly prescribed in the NICU for gastroesophageal reflux (GER), apnea and bradycardia, bronchopulmonary dysplasia, airway anomalies, and bowel anomalies. 1,2 The lack of high quality evidence in infants prevents consensus regarding use for airway anomalies 9,10 and bowel anomalies such as esophageal atresia, 7,11 which remain controversial. However, evidence clearly demonstrates no benefit from acid suppression for GER in term or preterm infants 12 -15 or apnea in premature infants.…”
mentioning
confidence: 99%
“…3,8,9 Wade et al 10 reported that 13% of the medications refilled for premature infants in the first year of life were reflux medications. However, concerns about the efficacy of these medications in infancy, 6,7,11 which include a lack of symptomatic response to acid suppression in controlled studies 12,13 and potentially serious complications such as necrotizing enterocolitis and bacteremia/sepsis, 14,15 have led to more judicious use of GER medications in the NICU setting.…”
Section: What This Study Addsmentioning
confidence: 99%